Letters from the Past: Justinas Marcinkevičius’ Letters to His Teacher Genovaitė Andrašiūnienė - Bandoriūtė-Leikienė, Salomėja (Acta humanitarica academiae Saulensis, 2023)
Nowadays, the long-standing communication by letters has changed a lot. A couple of decades ago, writing letters to another city, country or simply to someone who lives further away was a completely normal activity. Today, paper letters are usually only documents or postcards. Thus, it is interesting and meaningful to study letters as a disappearing form of communication. Researching letters is interesting for representatives of various branches of science. Investigating ego documents, especially letters, gives us an opportunity to find out more about the past communication, sender and receiver of the letter and the general discourse of the researched period. Reading letters, especially letters written by famous public figures, is interesting not only for the scientists, but also for the regular readers. Furthermore, it justifies the taboo set by social norms – prohibited reading of stranger’s letters.The subject of this article are the letters of the Lithuanian poet Justinas Marcinkevičius to his teacher Andrašiūnienė, written in 1949–1961, after leaving Prienai to study at Vilnius University. Andrašiūnienė was a famous intelligent of Prienai district, a teacher of the Lithuanian language, who financially and morally supported her talented students, including famous poet Marcinkevičius and linguist Jonas Kazlauskas. The leads of the existence of these letters circulated among the people of Prienai for many years, until a few years ago they accidentally came into poet’s family hands (Marcinkevičius himself did not know about the existence of these letters). There are 44 letters of Marcinkevičius to teacher Andrašiūnienė, which were written while he was studying at Vilnius University. 43 letters are perfectly preserved, but one is no longer legible, because a third of the text is damaged.The research of the letters reveals a close relationship between young poet Marcinkevičius and his teacher: a son-mother relationship. Marcinkevičius’ choice to call the teacher mother, mommy, confirms the fact that he is missing for mother’s care and attention (he lost his real mother in his early adolescence). Andrašiūnienė was not only a financial supporter, guardian, but also the first critic of the young poet’s writing. This critique significantly formed poets’ personality.The young poet’s letters reveal his talent for writing: the texts are fluent and literary. Also, there are a lot of stories about his achievements and creative downfalls. Marcinkevičius is carefully writing about his negative position towards the ideology of the time. It is interesting to read letters where Marcinkevičius is arguing and getting angry with his teacher. These letters reveal the rebellious side of the poet, which is completely unexpected. The opportunity to look at Marcinkevičius’ youth by reading his letters deepens the knowledge of the change of the poet’s work and the formation of his personality.
Keywords: Justinas Marcinkevičius; letters; self-documentation; communication; ego documents